PROSPECTS OF EXPANDING THE REVENUE BASE IN THE TRANSFORMATION PROCESSES OF COMMERCIAL BANKS - Ernazarov Narmet Saparbayevich (American Journals, 2025)
Issues such as strategic investors, adaptation to market principles, elimination of dependence on state funds and creation of equal competitive conditions are defined as the main directions of the banking system reform strategy. The transition of banks to this process requires changing their business models. This article is an important scientific and practical aspect in the process of expanding the income base of commercial banks in the process of transformation.
Keywords: Banking transformation, liquidity, business model, interest income, non-interest income, FinTech technologies, digital transformation.